Sexual segregation in timing of foraging by imperial shags (Phalacrocorax atriceps): is it always ladies first? - Harris, Sabrina; Raya Rey, Andrea Nélida; Phillips, Richard A.; Quintana, Flavio Roberto (Marine Biology)
The time seabirds have to forage is restricted while breeding, as time at sea must be balanced against the need to take turns with the partner protecting the nest site or offspring, and timing constraints change once the breeding season is over. Combined geolocator-immersion devices were deployed on eleven Imperial Shags (four males and seven females) in Argentina (43°04′S; 64°2′W) in November 2006 and recovered in November 2007. During the breeding season, females foraged throughout the morning, males exclusively in the afternoon, and variability between individuals was low. Outside the breeding season, both sexes foraged throughout the day, and variability between individuals was high. Timing differences may be explained by higher constraints on foraging or greater demands of parental duties experienced by the smaller sex, females in this case. Sexual differences in reproductive role, feeding habits or proficiency can also lead to segregation in timing of foraging, particularly while breeding. Fil: Harris, Sabrina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico; Argentina Fil: Raya Rey, Andrea Nélida. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Phillips, Richard A. British Antartic Survey; Reino Unido Fil: Quintana, Flavio Roberto. Wildlife Conservation Society; Estados Unidos. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico; Argentina